The Historical Semiotics of Hafez’s Poems - Sahraee, Reza Morad; Khayatan, Elham (Journal of History Culture and Art Research, 2017)
Semiotics is defined as the study of signs. It is a general field one branch of which is language. There are literary signs in literature, as part of language, that are encoded to provoke meaning. The signs or forms in Hafez’s poems will be assessed here to discover what meaning he has meant to convey. Failure in relating the right meanings to the signs deprive us from the right interpretation of the poems. Semiotic achievements can help us to study meaning related to the form. Saussure’s structural view and his overlooking context and cultural background and his proposed indissoluble link between form and meaning cannot in all cases provide us with the precise meanings of literary signs. Poststructuralists, on the other hand, postulate an unstable relationship between sign and meaning. According to them, under different circumstances different meanings can be attributed to signs. In the present research, the posed question was if taking cultural and historical background into account could shed light on providing us with the very meaning meant by the poet. Based on content analysis, the history of Hafez’s age as one aspects of culture as well as the achievements of modern semiotics were studied and then numerous signs Hafez has encoded in his poems were randomly assessed. The theoretical basis of the research is Juri Lotman’s cultural semiotics. His “semiosphere” refers to the whole semiotic signs within a culture. The Tartu School has had a tendency to cultural history and cultural anthropology. It was clarified that historical awareness of the age in which the poet has versified his poems can lead us to the precise meaning the poet has meant to convey.